Bhatara Banuwka (Sebutan Anumerta Raja Udayana) - I Wayan Wardha (Balai Arkeologi Yogyakarta, 1994)
In the course of ancient Balinese history which lasted for nearly seven centuries, there have been twenty-one changes of leadership in government. All of these kings, not all of them can be known about the place of residence. Several inscriptions indicate that after the death of a king a temple was built as his place of residence called bedharman. For example, the king of Ugrasena after his death was dharma in Air Madatu; King Gunapriyadharmapatni was dharma in Burwan, king Udayana was dharma in Banuwka, Marakata in Camara Anakwungsu in Jalu, and Jayapangus was dharma in Dharmahanyar.